THE BIOETHICAL REASONING AND SOCIAL RESPONSIBILITY IN THE STUDENTS OF THE RACES OF BUSINESS AREA OF PERU AND UNMSM CENTRAL LAKES COLLEGE OF MEXICO CULAGOS - Gutiérrez Huby, Ana María (2013)
This article has been prepared in order to summarize the results of the research study entitled: Bioethics. Integral component of corporate social responsibility in students majoring in Accounting and Administration careers of the universities of San Marcos, Peru and University Center of Los Lagos CULAGOS of Guadalajara – Mexico. The study was developed to investigate the interest in understanding the degree of existing bioethical reasoning in Undergraduate students in business careers in both universities. The main objective was to seek motivation in the University Community and especially to the boards of both centers in order to insert the subject as part of the integral education for future professionals in the business field. The most relevant results were: for students from both schools the corporate social orientation index leaned to the compliance with the legal and economic aspects. In relation to the consideration of what is a successful and socially responsible company, both centers considered that the economic characteristics prevail in the concept of being successful. And finally, as to being socially responsible is more important the ethical behavior displayed towards the needs of stakeholders.